Optimal corporate capital structure theiry : its implications for capital market development in Trinidad and Tobago - Seerattan, Dave Arnold ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Reviews the literature on optimal corporate capital structure theory and corporate financing patterns in Trinidad and Tobago in an atempt to glean some policy implications from capital market development.